Indywidualne interpretacje przepisów podatkowych – problemy natury prawnokonstucyjnej i prakseologicznej - Drozdowski, Edgar (Kwartalnik Prawa Podatkowego, 2015)
The article offers a critique of the institution of advance tax rulings with regards to the practical aspects of its functioning and its conformity to the constitution. The aim of the article is first of all to indicate particular doubts between advance tax rulings and art. 7, 32, 84 and 217 of the Constitution of the Republic of Poland. Secondly, the negative impact the advance tax rulings have on the functioning of both the tax administration and the administrative judiciary, especially the Financial Chamber of the Supreme Administrative Court. The article will conclude by presenting proposals that aim to eliminate or limit the issues regarding the functioning of advance tax rulings. The author proposes to eliminate the institution of advance tax rulings and offers alternative solutions that guarantee legal certainty in the application of the tax legislation. If the solutions are not feasible, the author offers ways of improving the functioning of the advance tax rulings.